From Resistance to Accommodation: The Emergence and Controversy of Jaringan Intelektual Muda Muhammadiyah (JIMM) - Najib, Muhammad Ainun; Abdurrahman, Dudung; Muttaqin, Ahmad (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2023)
This paper explores the emergence of the Jaringan Intelektual Muda Muhammadiyah (JIMM: Muhammadiyah Young Intellectual Network) as a response to the perceived stagnation of Islamic thought within Muhammadiyah. The discussion encompasses the historical challenges faced by Muhammadiyah, including the dominance of Western-oriented modernism, organizational routine, and resistance to change within the institution. The analysis delves into the controversies surrounding JIMM, as it faced resistance from various circles within Muhammadiyah, often labeled as “liberal” and accused of affiliating with the Liberal Islamic Network (JIL). The paper details the resistance encountered by JIMM, both institutionally and ideologically, including attempts to disband the network during the 46th Congress of Muhammadiyah in 2005. The paper also examines the shift in Muhammadiyah’s stance towards JIMM over time, from initial resistance to eventual accommodation within the organization’s structure and thought processes. The narrative concludes by highlighting Muhammadiyah’s evolving perspective on JIMM as a potential catalyst for intellectual regeneration within the Islamic organization.